AUTONOMIA NO TRABALHO DA ENFERMEIRA INTENSIVISTA: ESTUDO DAS REPRESENTAÇÕES SOCIAIS - Silva, Iranete Almeida Sousa; Cruz, Enêde Andrade; Ribeiro, Elisa Auxiliadora da França; Souza, Ednir Assis (Revista Baiana de Enfermagem‏, 2013)